PENGARUH PERENCANAAN PARTISIPATIF TERHADAP EFEKTIVITAS PEMBANGUNAN DI DESA SANGKUB I, KECAMATAN SANGKUB, KABUPATEN BOLAANG MONGONDOW UTARA (DANA DESA) - SIMON, YULIANTI; PANGKEY, MASJE; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2020)
The purpose of this study was to study participatory planning for development in the village of Sangkub I,Sangkub District, North Bolaang Mongondow District (Village Fund). This study used a quantitativemethod. Research respondents were 74 informants in Sangkub I village, Sangkub District, BolaangMongondow Regency North, instruments and data collection techniques used are questionnaires andstructured interviews (quide interviews), analytical techniques used to test the hypothesis of simple statisticalanalysis or product moment chore, ask for positive and significant influence on development, which meansthat participatory planning variables are factors be the determinant or determinant of development; 2) Themore well-planned participatory planning, the higher the level of development improvement, especially inSangkub I Village, Sangkub District, Bolaang Mongondow Utara Regency.Kata Kunci : Participatory Planning, Development Effectiveness, Village